High-efficiency gene transfer into nontransformed cells: utility for studying gene regulation and analysis of potential therapeutic targets. - Horwood, N; Smith, C; Andreakos, E; Quattrocchi, E; Brennan, F; Feldmann, M; Foxwell, B (2002)
The elucidation of the signalling pathways involved in inflammatory diseases, such as rheumatoid arthritis, could provide long sought after targets for therapeutic intervention. Gene regulation is complex and varies depending on the cell type, as well as the signal eliciting gene activation. However, cells from certain lineages, such as macrophages, are specialised to degrade exogenous material and consequently do not easily transfect. Methods for high-efficiency gene transfer into primary cells of various lineages and disease states are desirable, as they remove the uncertainties associated with using transformed cell lines. Significant research has been undertaken into the development of nonviral and viral vectors for basic research, and as vehicles for gene therapy. We briefly review the current methods of gene delivery and the difficulties associated with each system. Adenoviruses have been used extensively to examine the role of various cytokines and signal transduction molecules in the pathogenesis of rheumatoid arthritis. This review will focus on the involvement of different signalling molecules in the production of tumour necrosis factor alpha by macrophages and in rheumatoid synovium. While the NF-kappaB pathway has proven to be a major mediator of tumour necrosis factor alpha production, it is not exclusive and work evaluating the involvement of other pathways is ongoing.